1952
DOI: 10.3382/ps.0310022
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Vitamin B12 and Thyroprotein on Egg Production, Egg Weight, Shell Quality and Hatchability

Abstract: hybrids made after successive generations of setting. Iowa State Col. J. Sci. 9: 429-450. Jones, D. F., 1917. Dominance of linked factors as a means of accounting for heterosis. Genetics 2: 466-479. Lonnquist, J. H., 1950. The effect of selection for combining ability within segregating lines of corn. Agron.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
8
0

Year Published

1952
1952
2010
2010

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 35 publications
1
8
0
Order By: Relevance
“…A similar result occurs in the report of Savage et al (1952), who fed thyroprotein in conjunction with a ration containing 10% fish meal and 5% dried skim milk. The animal protein caused a considerable increase in hatchability over an all vegetable ration supplemented with potassium iodide.…”
Section: A Marsden R C Jennings and R S Martin Lane End Farm supporting
confidence: 86%
“…A similar result occurs in the report of Savage et al (1952), who fed thyroprotein in conjunction with a ration containing 10% fish meal and 5% dried skim milk. The animal protein caused a considerable increase in hatchability over an all vegetable ration supplemented with potassium iodide.…”
Section: A Marsden R C Jennings and R S Martin Lane End Farm supporting
confidence: 86%
“…Lillie, Olsen and Bird (1949) first demonstrated with the pure crystalline vitamin that vitamin B12 is essential for hatchability. The findings of these experimenters were confirmed by Carver and McGinnis (1950a, b); Olcese, Couch and Lyman (1950); and many others Couch et al, 1950;Hill et al, 1950;Milligan and Combs, 1950;Petersen et al, 1950Petersen et al, , 1952Petersen et al, a, b, 1953Peeler et al, 1951;Skinner et al, 1951;Savage et al, 1952;Yacowitz et al, 1952;and Mariakulandai and McGinnis, 1953). The findings of these experimenters were confirmed by Carver and McGinnis (1950a, b); Olcese, Couch and Lyman (1950); and many others Couch et al, 1950;Hill et al, 1950;Milligan and Combs, 1950;Petersen et al, 1950Petersen et al, , 1952Petersen et al, a, b, 1953Peeler et al, 1951;Skinner et al, 1951;Savage et al, 1952;Yacowitz et al, 1952;and Mariakulandai and McGinnis, 1953).…”
mentioning
confidence: 67%
“…Skinner et al (1951) fed an allvegetable diet to laying chickens in batteries and observed an increase in egg production when an "APF" supplement was added to the diet. On the other hand, Peeler et al (1951) and Savage et al (1952) obtained no increase in egg production when vitamin B12 was added to all-vegetable diets of hens in batteries. On the other hand, Peeler et al (1951) and Savage et al (1952) obtained no increase in egg production when vitamin B12 was added to all-vegetable diets of hens in batteries.…”
mentioning
confidence: 87%
“…The necessity of this vitamin for hatchability has been shown by Lillie et al (1949), Lindstrom et al (1949), Olcese et al (1950), , and Carver and McGinnis (1950). An indication that vitamin B 12 is required for egg production and egg weight was presented by Holmes and Kramer (1965), Griffith and Schexnailder (1972) and Savage et al (1952). Berg et al (1952) found that increasing the protein content of the diet from 11 to 1.…”
Section: Introductionmentioning
confidence: 95%